A new mud shrimp species of Calastacus (Crustacea: Decapoda: Thalassinidea) from the South China Sea - Komai, Tomoyuki; Lin, Feng-Jiau; Chan, Tin-Yam (Zootaxa, 2009)
A new mud shrimp species of the deepwater calocaridid genus Calastacus Faxon, 1893, C. inflatus, is described on the basis of a single specimen from the South China Sea off the Pratas Islands. It is unique in the genus in having a faint cervical groove on the carapace, lacking spiniform projection at the dorsolateral distal angle of the second segment of the antennal peduncle, the possession of only one spine on the ventral margin of the merus of the cheliped, and the unarmed suture on the uropodal exopod. With the addition of the present new species, two species of the genus are now known from the West Pacific.